2020
DOI: 10.3390/ijms21093375
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Zinc Chelator, 1H10, Ameliorates Experimental Autoimmune Encephalomyelitis by Modulating Zinc Toxicity and AMPK Activation

Abstract: Previous studies in our lab revealed that chemical zinc chelation or zinc transporter 3 (ZnT3) gene deletion suppresses the clinical features and neuropathological changes associated with experimental autoimmune encephalomyelitis (EAE). In addition, although protective functions are well documented for AMP-activated protein kinase (AMPK), paradoxically, disease-promoting effects have also been demonstrated for this enzyme. Recent studies have demonstrated that AMPK contributes to zinc-induced neurotoxicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Clioquinol (CQ) and ZnT3 gene deletion were shown to significantly suppress EAE (an animal model of MS)-associated clinical features and neuropathological changes, as well as inhibit MMP-9 activation, BBB disruption and immune cell infiltration, implying the involvement of synaptic Zn 2+ in myelin damage of spinal cord white matter [227,228]. Likewise, similar results were also found in a recent study using 1H10, a novel Zn 2+ chelator [229].…”
Section: Zn 2+ and Multiple Sclerosissupporting
confidence: 69%
“…Clioquinol (CQ) and ZnT3 gene deletion were shown to significantly suppress EAE (an animal model of MS)-associated clinical features and neuropathological changes, as well as inhibit MMP-9 activation, BBB disruption and immune cell infiltration, implying the involvement of synaptic Zn 2+ in myelin damage of spinal cord white matter [227,228]. Likewise, similar results were also found in a recent study using 1H10, a novel Zn 2+ chelator [229].…”
Section: Zn 2+ and Multiple Sclerosissupporting
confidence: 69%
“…Our lab reported that excessive vesicular zinc released from presynaptic terminals and subsequent zinc accumulation into post-synaptic neurons induced multiple neuron death cascades, such as reactive oxygen species (ROS) production and poly(ADP-ribose) polymerase-1 (PARP-1) activation [ 45 , 46 ]. We also demonstrated that microglia activation and MMP-9 activation induced BBB disruption, which is also involved in zinc toxicity in the brain [ 41 , 47 , 48 ]. Cytoplasmic zinc increases were prevented by the intracerebroventricular (i.c.v) injection of the zinc chelator, CaEDTA [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…1H10 is an inhibitor of AMP-activated protein kinase (AMPK) phosphorylation, and it was experimentally demonstrated that 1H10 also has the ability to chelate Zn 2+ . Intraperitoneal injection of 1H10 in mice inhibited EAE-induced demyelination and microglia/macrophage activation, inhibited EAE-induced MMP-9 activation and zinc plaque formation and alleviated multiple sclerosis (MS) [ 85 ]. Therefore, inhibition of AMPK phosphorylation or chelation of Zn 2+ may be an effective target for MS treatment.…”
Section: Zinc Homeostasis and Neuroinflammatory Diseasesmentioning
confidence: 99%